Relationship of bizygomatic and bigonial breadth with the suitability of surgical masks - Nany Hairunisa; Lie T. Merijanti; Alvin M. Ridwan; Diana Samara; Magdalena Wartono; Ridwan Harrianto (Universitas Gadjah Mada, 2023)
Use of masks is mandatory to prevent the transmission of COVID-19. Appropriate masks that match the face size is very important to avoid leakage. This study aimed to evaluate the relationship between bizygomatic and bigonial breadth with the suitability of surgical masks. It was an analytic observational study with a cross-sectional design conducted at the Occupational Medicine Laboratory, Faculty of Medicine, Universitas Trisakti, Jakarta during March to April 2021. A total 132 employees of Faculty of Medicine, Universitas Trisakti aged from 20 to 64 y.o. who meet the inclusion and exclusion criteria participated in this study. No significantly difference in age (p=0.248) and body mass index (BMI) (p=0.226) was observed. However, there was a significantly difference in bizygomatic width (p=0.000) and bigonial width (p=0.001) between men and women. The use of appropriate surgical masks was observed in 89 respondents, but not suitable for 43 respondents. There was no significantly difference between BMI, bizygomatic width and bigonial width with the suitability of surgical masks. However, old age was significantly more appropriate for using surgical masks than young people. In conclusion, BMI, bizygomatic width, and bigonial width are not substantially different with the suitability of surgical masks. However, older age is more suitable for employing surgical masks than younger age.